The amazing book of Marvel Spider-Man - Grange, Emma (New York, New York DK Publishing, 2017)
Introduces Spider-Man, providing details on how he got his power and who his allies and enemies are
"Includes gigantic poster of Spider-Man plus fun fold-out pages"--Cover
Comic Strips
1
Keywords: Spider-Man -- (Fictitious character) -- Juvenile literature; Spider-Man -- (Fictitious character); Spider-Man -- (Fictitious character); Lift-the-flap books -- Specimens; Lift-the-flap books; Toy and movable books; Lift-the-flap books; Juvenile works; Specimens